(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: Research title: Bullying Behavior in Children (Concept - Causes – Treatment) This research aimed to identify the concept of bullying behavior, the history of the study of bullying, to identify the types of bullying, the extent of the phenomenon of bullying, to identify the causes of the phenomenon of bullying widespread among children, the causes that lead to the occurrence of the phenomenon of bullying in children, and to identify the theories explaining the behavior of bullying, the consequences and effects of the victims of bullying, and to identify the treat the phenomenon of bullying in children. Research Methodology: The researcher used the descriptive library approach in this paper. Research tool: The research tool consisted of books, references, studies, educational research, periodicals and scientific journals that dealt with this topic. The results of the research concluded that bullying is a pathological phenomenon that is widespread in societies and is constantly increasing, and perhaps one of the most important causes of bullying is the lack of awareness in society, and bullying occurs in different and multiple forms and also with different levels in the severity of abuse. There are many reasons and factors that lead to the formation of bullying behavior among children, including psychological, social, personal, scholastic, and reasons related to media. Bullying behavior has harmful effects on child victims, as well as bullies. Victims also suffer from feelings of fear, insecurity, lack of calmness, psychological stability, and isolation from others. The researcher recommends building educational and counseling programs to help children face the behavioral problems they live with, develop the religious and spiritual motives of bullying children, and teach them moral principles so that they can be good children and loved by others.